2022
DOI: 10.3389/fpls.2022.960723
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide comparative analysis of the nucleotide-binding site-encoding genes in four Ipomoea species

Abstract: The nucleotide-binding site (NBS)-encoding gene is a major type of resistance (R) gene, and its diverse evolutionary patterns were analyzed in different angiosperm lineages. Until now, no comparative studies have been done on the NBS encoding genes in Ipomoea species. In this study, various numbers of NBS-encoding genes were identified across the whole genome of sweet potato (Ipomoea batatas) (#889), Ipomoea trifida (#554), Ipomoea triloba (#571), and Ipomoea nil (#757). Gene analysis showed that the CN-type a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Studies have found that some wild species are better able than cultivated species to resist biotic and abiotic stresses [ 73 , 74 , 75 ]. Therefore, the diploid relatives are valuable resources for the improvement of cultivated sweet potato [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that some wild species are better able than cultivated species to resist biotic and abiotic stresses [ 73 , 74 , 75 ]. Therefore, the diploid relatives are valuable resources for the improvement of cultivated sweet potato [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…These genome data contribute to the genetic study of sweet potatoes and genome evolution analysis in the Ipomoea species. In a previous study, some important enzyme-encoding genes (such as XTH, NBS, CDPK, SWEET, and SPL) [59][60][61][62][63] and TFs (such as GRAS, WRKY, bZIP, and MADS-box) [64][65][66][67][68] gene families were investigated in tuberous root development and the stress responses of Ipomoea species. However, a comprehensive and comparative molecular, evolutionary, and functional analysis of R2R3-MYB genes, which are indispensable for several developmental pathways and stress responses, is lacking in the Ipomoea species, even though the R2R3-MYB gene family has been identified in I. aquatica [69] and I. nil [70].…”
Section: Discussionmentioning
confidence: 99%
“…An interspecific collinearity analysis of R2R3-MYBs showed that a total of 1223 collinearity gene pairs were detected among hexaploid I. batatas and 5 other diploid Ipomoea species, but their collinearity relationships were not as good as expected. Given their species' phylogenetic relationships (Figure 5a), one reasonable explanation is that the hexaploid I. batatas genome might have undergone a larger chromosome rearrangement during the evolutionary process [60].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 11 differentially expressed NBS genes were found in Tengfei and JK20 after infection by stem nematodes, and 19 differentially expressed NBS genes were found in Santiandao and JK274 after infection by C. fimbriata, respectively. These results will provide a reference for the exploration of sweet potato disease resistance genes [45]. Yan et al used sweet potato cv.…”
Section: Exploration Of Resistance Genes In Sweet Potato For Nematode...mentioning
confidence: 96%